THE RELATIONSHIP BETWEEN TIME AND WATER CONTENT OF FISH DRIED USING SOLAR PANEL-BASED DRYERS - Sutrisno Sutrisno; Rindang Wahyu Puspitasari; Anang Pamungkas; Daeng Achmad Suaidi (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
Traditional drying of fish, the water content produced is not in accordance with SNI (Indonesian National Standard), which is less than 40%. This research aims to determine the correlation between time and water content of fish dried with an electric-based fish dryer produced from solar panels. The method used is a quantitative method. The solar panel-based electric fish dryer has a maximum capacity of 2237 grams (12 fish) with a temperature above 30°C. Based on the data analysis, the correlation between time and water content was obtained, the results for the 1st, 2nd and 3rd experiments, the average correlation coefficient was R² = 0.99, and the correlation between the mass of dried fish and the water content of fish, the more mass of fish that is dried the more water content evaporates (dry), To meet the water content of fish that is permitted according to SNI, which is less than 40%, it takes a long time to dry. about 4 days. The heating system in the drying chamber was based on the first experiment until the third experiment, the heat was evenly distributed and quite good in the drying chamber, so that the temperature control system worked well. This solar panel-based fish drying system can be used by fishermen to lighten fish in improving the quality of their products according to SNI.